Il diritto come mediazione fra saperi distinti. Perché il diritto non ha fatto un passo indietro di fronte alla scienza (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Il diritto resiste alla scienza - 2. La scienza come criterio di legittimazione della norma giuridica - 3. Diritto come fenomeno normativo: incommensurabilità fra diritto e scienza - 4. Il diritto come super scienza - 4.1. Voracità processuale - 4.2. Verità giuridica e legittimazione dell’organo decidente - 4.3. Verità giuridica e falsificazione - 4.4. Margini del sindacato giudiziario - 5. Diritto come mediazione fra saperi distinti - 6. Conclusioni: diritto, scienza e gestione dell’incertezza.Law as system which incorporates distinct epistemological methods. Why legal reasoning did not retreat before scientific knowledgeABSTRACT: The central claim of this Article is that, despite the frequent references by legal acts to scientific knowledge, the scientific method has not supplanted or overshadowed the proper features of legal reasoning arising from the idea of law as an autonomous system of knowledge. In fact, just the opposite has occurred. It will be argued that the resistance of the legal at the scientific method can be explained on the basis of three distinct theories of law and legal reasoning: a) the first claims that law is a normative system which is incommensurable with science; b) the second qualifies law as a kind of superscience which grounds legitimacy to science itself; c) the third defines law as a normative system which accepts and incorporates forms of knowledges which the scientific method normally rejects.